Unaddressed participants’ gaze in multi-person interaction: optimizing recipiency - Holler, Judith; Kendrick, Kobin H. (Frontiers in Psychology, 2015)
One of the most intriguing aspects of human communication is its turn-taking system. It requires the ability to process on-going turns at talk while planning the next, and to launch this next turn without considerable overlap or delay. Recent research has in-vestigated the eye movements of observers of dialogues to gain insight into how we process turns at talk. More specifically, this research has focused on the extent to which we are able to anticipate the end of current and the beginning of next turns. At the same time, there has been a call for shifting experimental paradigms exploring social-cognitive processes away from passive observation towards on-line processing. Here, we present research that responds to this call by situating state-of-the-art tech-nology for tracking interlocutors’ eye movements within spontaneous, face-to-face conversation. Each conversation involved three native speakers of English. The anal-ysis focused on question-response sequences involving just two of those participants, thus rendering the third momentarily unaddressed. Temporal analyses of the un-addressed participants’ gaze shifts from current to next speaker revealed that un-addressed participants are able to anticipate next turns, and moreover, that they often shift their gaze towards the next speaker before the current turn ends. However, an analysis of the complex structure of turns at talk revealed that the planning of these gaze shifts virtually coincides with the points at which the turns first become recog-nizable as possibly complete. We argue that the timing of these eye movements is governed by an organizational principle whereby unaddressed participants shift their gaze at a point that appears interactionally most optimal: It provides unaddressed participants with access to much of the visual, bodily behavior that accompanies both the current speaker’s and the next speaker’s turn, and it allows them to display recipiency with regard to both speakers’ turns.